2000
DOI: 10.1046/j.1468-1331.2000.00128.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical epidemiology of Guillain–Barré syndrome in adults in Sweden 1996–97: a prospective study

Abstract: We described clinical manifestations, outcomes, prognostic indicators and clinico-epidemiological subgroups for 53 adult patients with Guillain-Barré syndrome (GBS) in Sweden during the period 1996-97. These patients were identified from a population of 2.8 million inhabitants and prospectively followed up for one year by a network of neurologists. An additional 10 cases, of whom five were adults who had not been prospectively followed up, were not included in the analyses. At 6 months after onset 80% of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
28
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 36 publications
8
28
2
1
Order By: Relevance
“…Campylobacter jejuni , a gastrointestinal infection, is the most commonly identified antecedent infection among GBS cases [5]; however, recent studies have also found an increased risk of GBS in the period immediately following influenza-like illness [10,26,27]. Our results show a higher proportion of patients treated with intravenous immune globulin (74%) compared with older studies (30–40%) [3], reflecting the shift in treatment preference following randomized control results which show that IgIV has similar efficacy to plasma exchange and is more convenient to administer [5]. The clinical course of GBS in our study was in agreement with that from other case series [5].…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Campylobacter jejuni , a gastrointestinal infection, is the most commonly identified antecedent infection among GBS cases [5]; however, recent studies have also found an increased risk of GBS in the period immediately following influenza-like illness [10,26,27]. Our results show a higher proportion of patients treated with intravenous immune globulin (74%) compared with older studies (30–40%) [3], reflecting the shift in treatment preference following randomized control results which show that IgIV has similar efficacy to plasma exchange and is more convenient to administer [5]. The clinical course of GBS in our study was in agreement with that from other case series [5].…”
Section: Discussioncontrasting
confidence: 45%
“…A comprehensive review estimated GBS incidence rates in North America and Europe to be between 1–2 per 100,000 person-years [2]. The rate increases with age and male sex [2,3,4]. Strong seasonal associations or clear secular trends in GBS rates have not been documented [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…Mortality rate ranges from 2-13% in different studies. Dana I, et al 22 study shows 5%, Italian GBS study group shows (up to 12%), Cherg Q, et al (2000) 18 shows 8%, Nicholas, et al (1998) 20 shows 4%, Italian study (1988-93) 9%, South England (1993-94) shows 9%,Voston MGH (1962-81) shows 2%, Brazil study (2003) shows 10% mortality among all GBS case. In our study mortality rate was 7% which is comparable to other studies.…”
Section: Discussionmentioning
confidence: 95%
“…This is of interest because GBS is a disorder that is reportedly more common in males than females [48]. Furthermore, GBS is thought to be an autoimmune disorder, and presumably patients develop GBS because they have T cell or antibody reactivity to an antigen important in GBS.…”
Section: Discussionmentioning
confidence: 99%